2018
DOI: 10.1002/mrm.27495
|View full text |Cite
|
Sign up to set email alerts
|

T1 and T2 quantification from standard turbo spin echo images

Abstract: Purpose To extract longitudinal and transverse (T1 and T2) relaxation maps from standard MRI methods. Methods Bloch simulations were used to model relative signal amplitudes from standard turbo spin‐echo sequences: proton density weighted, T2‐weighted, and either T2‐weighted fluid attenuated inversion recovery or T1‐weighted images. Simulations over a range of expected parameter values yielded a look‐up table of relative signal intensities of these sequences. Weighted images and flip angle maps were acquired i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…From a practical point of view, multi‐slice acquisitions are designed to alleviate MT DIR effects related to slice‐profile imperfections by interleaving the slice order. This means that instead of acquiring slices sequentially (i.e., ascending or descending order), the series of odd‐numbered slices are acquired first and then the even‐numbered slices …”
Section: Discussionmentioning
confidence: 99%
“…From a practical point of view, multi‐slice acquisitions are designed to alleviate MT DIR effects related to slice‐profile imperfections by interleaving the slice order. This means that instead of acquiring slices sequentially (i.e., ascending or descending order), the series of odd‐numbered slices are acquired first and then the even‐numbered slices …”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, for many quantitative MRI methods, flip‐angle precision in each voxel is needed. Examples include T 1 and T 2 mapping and quantitative magnetization transfer, in which substantial errors can arise without accurate flip‐angle knowledge and inclusion in the modeling process 6–11 . Therefore, a B1+ map can be beneficial to measure the exact flip angle in each voxel using one of several different methods, including double‐angle method, 12,13 Bloch‐Siegert shift, 14 actual flip‐angle imaging 15 or dual refocusing echo acquisition mode 16 …”
Section: Introductionmentioning
confidence: 99%
“…The lack of B1+ maps in many studies arises from the additional scan time required on the order of 1 min, although methods are becoming faster, 17,18 and the irrelevance of B1+ mapping to interpretation of standard weighted images currently dominating clinical practice. However, production of quantitative MRI maps from weighted images would require B1+ map knowledge 10,19 . When B1+ maps are not available, the use of large experimental B1+ data sets may aid in predicting B1+ maps to enable more accurate quantitative maps, particularly for maps derived from clinical or retrospective data 20 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, other methodologies have been suggested that T 2 accuracy is greatly improved by matching the MSE signal to a precomputed EMC dictionary 13,14,16 . In many cases, T 1 estimation may also be of interest and accurate knowledge of the B1+ field is required to minimize estimation errors 21 . Although some studies have explored B1+ estimation with either separate scanning or by joint estimation, many are still limited to research‐only and/or specifically pulse‐programed sequences.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it would be of great interest to perform simultaneous multiparametric estimation (here focused on B1+ and T 2 ) with standard clinical protocols (such as the MSE). A similar idea was also explored showing quantification of T 1 and T 2 from standard turbo spin‐echo protocols 21,22 …”
Section: Introductionmentioning
confidence: 99%